The Synergy between Minority Business Enterprises and Corporations: A Proposed Supplier Diversity Relationship Framework - Erastus Ndinguri; Leon Prieto; Simone Phipps; Vicky Katsioloudes (International Journal of Supply Chain Management, 2013)
Relationships between businesses as customers and suppliers have been an area of research for a long time (Hkansson, 1982; Hkansson Snehota, 1995). Some of the interacting business relation entities include corporations, small businesses, consumers and minority business enterprises. Through the years the growth of Minority Business Enterprise (MBE) movement in the United States can be traced from the 1970s when President Nixon opened the first Office of the Minority Business Enterprise. Today Minority Business Enterprises in the United States are classified as businesses that are owned and controlled by individuals identified as minorities (National Minority Supplier Diversity Council, 2011; Shah Ram, 2006). Growth is evident in underrepresented fields such as construction, industries and wholesale (Bates, 2001). This growth has led to stronger relationships between more corporate partners and MBEs (National Minority Supplier Diversity Council, 2011). Through the National Minority Supply Development Council Network (NMSDC), MBEs are connected to 3,500 corporate members including Americas top publicly-owned, privately-owned and foreign-owned companies, as well as universities, hospitals and other buying institutions (National Minority Supplier Diversity Council, 2011). To sustain this growth, the relationships between the corporate member participants and the MBEs require cultivation. Yet, no documented framework describes the relationships which are crucial to this growth. Therefore, this paper proposes to enhance the discussion on MBE-Corporation relationship. The paper explores the importance of MBE-Corporation relationship in expanding MBEs. In addition the paper develops an initial conceptual MBE-Corporation relationship framework that explains the different conceptual levels that lead to attaining and maintaining such a relationship.